SOSIALISASI PROGRAM JKN KIS DAN PEMANFAATAN APLIKASI MOBILE JKN DI KABUPATEN TUBAN - eva silviana rahmawati; M. Sudrajad; Sugiyono; Muhaimin Ilham Lahiya (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2024)
This article discusses problems related to the lack of public knowledge regarding the use of health services from the National Health Insurance Program (JKN) Healthy Indonesia Card (KIS). Using a theoretical approach from researchers, this article details socialization steps as a strategy to increase community understanding and participation in utilizing this program. National Social Security (SJSN). The National Social Security System is implemented through a mandatory Social Health Insurance mechanism based on Law No. 40 of 2004 concerning the National Social Security System. The aim of this research is to find out what the public's knowledge is about the JKN program. research method using interviews with local communities and observations and adding several questionnaires to increase accuracy. From the results of the discussion and research, it can be concluded that there are still many people who do not know about the JKN program and what BPJS is and the benefits of BPJS and what payment methods are for independent individuals and how to register for BPJS. And there are some people who sometimes have already paid and don't pay anymore and people don't know what action to take, whether to continue paying or don't need to pay anymore, because from the community's point of view, they have never received services from BPJS because they have never been treated at the nearest health center or hospital. .and from the results of the interview we can conclude that knowledge has a great influence on the public's view of BPJS services